Seismic Vulnerability Assessment of Soft-Storey Structure: Insights from Nonlinear Pushover Analysis - Badhon Singha; Mohammad Atiqur Rahman Sakib (Platform, a Journal of Engineering, 2025)
Buildings with open ground floors, often used for parking or commercial purposes, and brick walls on the upper levels have distinct vulnerabilities during earthquakes. These structures are typically designed as frame systems without considering the stiffness provided by the brick walls, which creates a significant weakness at the ground floor level when subjected to seismic activity. This study focuses on understanding how such weaknesses affect ground floor columns by conducting a nonlinear static pushover analysis on various building models. The models differ in their bay and span configurations and the extent to which brick walls are included. The findings reveal that weak ground-floor buildings experience notably higher forces and stresses in their ground-floor columns, which increases the likelihood of premature failure during seismic events. To address this issue, the study suggests increasing the design forces and stresses for ground floor columns to compensate for the absence of brick walls. This approach aims to reduce potential risks and enhance the overall seismic performance of these structures.